Mean Platelet Volume-To-Lymphocyte Ratio Predicts Poor Functional Outcomes Among Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Chen, Si-Yan; Lin, Yuan-Shao; Cheng, Yi-Fan; Wang, Hong; Niu, Xiao-Ting; Zhang, Wan-Li (Frontiers in Neurology, 2019)
Background and Purpose: According to previous studies, the mean platelet volume-to-lymphocyte ratio (MPVLR) represents a novel marker of a poor short-term prognosis in patients with a myocardial infarction who underwent a primary percutaneous coronary intervention. We aimed to evaluate the association between MPVLR and clinical outcomes of patients with acute ischemic stroke who were treated with intravenous thrombolysis. Methods: Two hundred forty-one patients with ischemic stroke receiving intravenous thrombolysis were prospectively enrolled in this study. Blood samples for MPVLR were obtained at admission and at 18-24 h after treatment with intravenous thrombolysis. A poor functional outcome was defined as a modified Rankin Scale (mRS) score of 3-6 at 3 months after stroke. Results: At admission, the area under the curve (AUC) of MPVLR to predict poor functional outcomes at 3 months was 0.613 (95% confidence interval [CI], 0.541-0.686; P=0.003), and the best predictive MPVLR value was 5.8. Patients with an MPVLR ≥5.8 had a 3.141-fold increased risk of a poor outcome at 3 months (95% CI , 1.491-6.615; P=0.003) compared to patients with an MPVLR <5.8. At 18-24 h after treatment with intravenous thrombolysis, the AUC of MPVLR to predict a poor outcome at 3 months was 0.697 (95% CI, 0.630-0.765, P<0.001), and the best predictive MPVLR value was 6.9. The inclusion of MPVLR as a continuous (OR 1.145; 95% CI, 1.044-1.256, P=0.004) and categorical variable (OR 6.555; 95% CI, 2.986-14.393, P<0.001) was independently associated with poor outcomes at 3 months. Conclusions: Both the values of MPVLR at admission and 18-24 hours after intravenous thrombolysis were independently associated with poor functional outcomes. MPVLR may serve as an activity marker for a poor prognosis in patients with acute ischemic stroke receiving intravenous thrombolysis.